Control of the National Superintendency of Customs and tax administration in tax works, 2019 - Ortiz Basauri, Carmen Eufemia (2021)
Objective: To contribute to the strengthening SUNAT’s tax administration control system in public investment projects that are executed in Peru through the mechanism of works for taxes. Method: The research was quantitative, has an explanatory and descriptive range, it is non-experimental, and possesses a cross-sectional and documental design. The sample was made up of 50 former SUNAT officials who, in November 2019, were surveyed on 16 items with an evaluative response of 5 alternatives. Results: The research’s results indicate that 80% of the participants fully agree with the implementation of a preventive, concurrent, and subsequent control; 20% agree, and 10% of them are indifferent to the matter; this resonates with the theoretical expectation. Conclusion: The proposal explains, by an average of 80%, that the perception of the 50 former SUNAT officials about the strengthening of the SUNAT’s control system with the implementation of a preventive, concurrent, and subsequent control, will strengthen the mechanism of works for taxes.